Of the technique as poetics: a chiasm of dance from Michel Bernard (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The present manuscript is part of the still unpublished ongoing PhD research developed in the Post-Graduation Program in Education of the Federal University of Ceará, which performs an investigation along with the translation to the Portuguese of the seminal work De la Création Chorégraphique de Michel Bernard (2001). The text comprehends the critical Introduction of the thesis and proposes considerations in the search of entangle the philosophical and pedagogical practices in dance from the philosophical thinking. It has been investigated conceptual bonds that aim to collaborate for a comprehension of the techniques in dace which are immanent to the sensory-perceptual processes of the bodily experience. The experimentation presented here relate central notions of the author’s work – dancing corporeality, orchesality and the author’s fictioning theory of sensation- as a fertile ground to rethink the teaching of the technical knowledge in dance, making them as one of the imbricate aspects of the poetics of the dance. To think technique as poetics has been our goal.
Keywords: Dance technique; Poetics of corporeality; Michel Bernard; Dance pedagogy